Code switching and code mixing used by teachers in teaching procedure text - Anna Estu Wijayati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2022)
This study aims to describe 1). Types of code switching and code mixing used by teachers in teaching procedural texts, and 2). Reasons for using code switching and code mixing in procedural text at SMK Cendekia Madiun. The method used is descriptive qualitative. The results showed, 1) types of code switching There are three types of code switching used, namely the tag switching type appears 3 times, the inter-sentential type appears 3 times and the intra-sentential type appears 5 times. Meanwhile, there are 2 types of code mixing. 2) The researcher reports that the reason teachers use language mixing and language transfer is to make it easier for students to understand instructions in procedural texts, so that students are able to make procedure texts independently. The conclusion of this study is that code switching and code mixing are usually done because of multilingualism and clarification in conveying the meaning of the material conveyed by the teacher in the procedure text. This is done by teachers and students so that learning can run smoothly, comfortably and students understand the procedure text presented.